The Cascades painted stones - Swart, J.; Escott, B. (Southern African Humanities, 2021)
A collection of painted stones was discovered amongst a cluster of boulders at Cascades 2 in the uKhahlamba-Drakensberg Park. All four stones have residues of paint and pigment; one has paintings of what appear to be four rhebuck. We describe the stones and briefly consider their significance. Interpretation is necessarily limited by the surface context of the find. Nevertheless, we suggest that for the southeastern San the stones may have facilitated access to the spirit world. To cite this article: Swart, J. & Escott, B. 2003. The Cascades painted stones. Southern African Humanities 15: 75-89.